2021
DOI: 10.21203/rs.3.rs-1161642/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Ketoconazole On Clinical Recovery In Central Serous Chorioretinopathy

Abstract: Background: Hypercortisolism has long been correlated with choroidal vasorelaxation in central serous chorioretinopathy (CSCR). This may explain the inconsistency of therapeutic responses of the mineralocorticoid receptor (MR) antagonist since hyperaldosteronism has rarely been detected in such cases. Hence, an early treatment using ketoconazole, the first line cortisol inhibitor that also blocks the MR ligand, appears to be rational. This study aimed to evaluate the effects of ketoconazole on CSCR, and to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
0
3
0
Order By: Relevance
“… 31 In a retrospective cohort study with a total of 41 naive CSC eyes, it was found that ketoconazole treatment could shorten the disease duration through promoting SRF absorbtion. 32 Another effective glucocorticoid antagonist, mifepristone, was used in CSC treatment. Mifepristone 200 mg was administered orally to 16 chronic CSC cases and showed that systemic glucocorticoid receptor antagonism promoted improvement and remission of retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“… 31 In a retrospective cohort study with a total of 41 naive CSC eyes, it was found that ketoconazole treatment could shorten the disease duration through promoting SRF absorbtion. 32 Another effective glucocorticoid antagonist, mifepristone, was used in CSC treatment. Mifepristone 200 mg was administered orally to 16 chronic CSC cases and showed that systemic glucocorticoid receptor antagonism promoted improvement and remission of retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…After 4 weeks of treatment, the treatment and control groups demonstrated no significant change in BCVA or pigment epithelial detachment thickness. In a recent study by Chantarasorn et al [12], the efficacy of ketoconazole 400 or 600 mg per day was evaluated in 21 patients and compared to 20 patients who served as controls. Ketoconazole shortened the time to resolution (7 vs. 16 weeks; p < 0.01) and reduced the need for rescue laser treatment (23.8% vs. 50%; p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Case Reports in Ophthalmology toward an anti-steroid effect of terbinafine [10]. The effect of other antifungal medications such as ketoconazole on CSCR has been previously explored as well; however, data have been inconsistent [11][12][13]. Meyerle et al [13] reported on 5 patients with CSCR treated for 4 weeks with ketoconazole 600 mg/day.…”
Section: Discussionmentioning
confidence: 99%